Implementasi Model Pembelajaran Problem Based Learning Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Di SMA Islam Perlaungan Waru Sidoarjo - M. Taufiq Bawazier; Yuliastutik Yuliastutik (Jurnal Budi Pekerti Agama Islam, 2024)
The Problem Based Learning learning model is a learning model that begins with giving problems to students where the problems given are everyday experiences or have been experienced by students. Then students solve the problems given to gain new knowledge. It is expected that students are able to learn knowledge related to these problems, as well as students have skills in solving problems. The purpose of this research is to increase student motivation in PAI subjects at Perlaungan Islamic High School. The research method used is descriptive qualitative. The data collection techniques used are in-depth interviews, observation and documentation. Data analysis was carried out through data reduction, data presentation and then drawing conclusions. The sources of data in this study are school principals, deputy heads of curricula, PAI teachers, and students. The results of the study show that: 1. Implementation of the Problem Based Learning learning model in PAI subjects at Perlaungan Islamic High School there are five stages, namely, student orientation to problems, organizing students to learn, guiding educators to search for data on a problem, developing and presenting the work , analyze and evaluate. 2. Student learning motivation, there are two learning motivations, namely, intrinsic motivation, intrinsic motivation there are three indicators namely, there is a desire and desire to succeed, there are encouragement and needs in learning, there are hopes and ideals, and extrinsic motivation, there are five extrinsic motivations indicators namely, there is appreciation in learning, there are interesting activities in learning, there is a conducive learning environment, teacher-student relationships, student-student relationships.